THE EFFECT OF COMPANY SIZE AND DER ON ROA AND COMPANY VALUE IN THE FOOD AND BEVERAGE SUB SECTOR ON THE INDONESIA STOCK EXCHANGE (IDX) - Teddy Chandra; Harry Patuan Panjaitan; Sari (Institut Bisnis dan Teknologi Pelita Indonesia, 2021)
This research use firm size variable, capital structure to profitability and company value. Selection of four variables because there are differences in previous research or commonly called the research gap. The purpose of research to determine the effect of firm size, structure capital to profitability and the value of the company in food and beverage companies in Indonesia Stock Exchange. The population in this study used the company food and beverage sector 23 companies, with a sample size of 17 companies. This research uses descriptive statistical analysis methods, multicollinearity test hypothesis testing and data analysis of the coefficient of determination. The results of the analysis found that (1) firm size has negative effect not significant to profitability. (2) capital structure has positive effect significant to profitability. (3) firm size has negative effect not significant to firm value. (4) capital structure has negative effect significant to firm value. (5) profitability has positive effect significant to firm value.